Hashimoto’s Thyroiditis and Autoimmune Gastritis - Cellini, Miriam; Santaguida, Maria Giulia; Virili, Camilla; Capriello, Silvia; Brusca, Nunzia; Gargano, Lucilla; Centanni, Marco (Frontiers in Endocrinology, 2017)
The term ‘thyrogastric syndrome’ defines the association between autoimmune thyroid disease and chronic autoimmune gastritis and it was firstly described in the early 1960s. More recently, this association has been included in polyglandular autoimmune syndrome type IIIb (PAS IIIb), in which autoimmune thyroiditis represents the pivotal disorder. Hashimoto’s thyroiditis is the most frequent autoimmune disease and it has been reported to be associated to gastric disorders in 10 to 40% of patients while about 40% of patients with autoimmune gastritis also present Hashimoto’s thyroiditis. Some intriguing similarities have been described about the pathogenic mechanism of these two disorders, involving a complex interaction among genetic, embryological, immunologic and environmental factors. Chronic autoimmune gastritis is characterized by a partial or total disappearance of parietal cells implying the impairment of both hydrochloric acid and intrinsic factor production. The clinical outcome of this gastric damage is the occurrence of a hypochlorhydric-dependent iron-deficient anemia, followed by pernicious anemia concomitant with the progression to a severe gastric atrophy. Malabsorption of levothyroxine may occur as well. We have briefly summarized in this minireview the most recent achievements on this peculiar association of diseases that, in the last years, has been increasingly diagnosed.